Children computer mouse use and anthropometry. - Soares, Marcelo M.; Jacobs, Karen; Hughes, Erin E.; Johnson, Peter W. (Work)
Studies have shown that increased computer use among adults in occupational settings is associated with the development of cumulative trauma disorders; however, the need to address how adult-sized mice and keyboards are affecting children is becoming increasingly important as both access to and use of computers is increasing among today's youth. To address the potential mismatch that exists between child stature and computer input device size and activation force, we have applied existing, age-specific, anthropometric data to elements of device design, including mouse size (length, width, height, switch location), and mouse-button activation forces. Trends supported the development of smaller computer input devices with lower activation forces for smaller statured individuals including children. Distinct and consistent trends in size delineations were seen across gender and age groups-trends that correlate well with grades and schooling in the United States education system . Three to four mouse sizes would be recommended: a mouse sized for adult and high school males; one for adult and high school females and junior high males; one for elementary school children, aged 6 to 10 years; and possibly a mouse for the smallest users who are less than six years old.